Hallelujah lads & lasses : remaking the Salvation Army in America, 1880-1930 - Taiz, Lillian (University of North Carolina Press, 2001)
Placing her focus on the membership of the Salvation Army and its transformation as an organization within the broader context of literature on class, labour and women's history, Taiz reveals the character of American working-class culture and religion in the late 19th and early 20th centuries.